Experimental and numerical investigation on failure behavior of ring joints in precast concrete shear walls. Issue 1 (January 2020) - Zhou, Jian; Zhi, Xudong; Fan, Feng; Jiao, Anliang; Qian, Hongliang
Precast shear wall structures have been widely used due to their outstanding features, and the joints between precast members play a critical role in complete structures, specifically for vertical joints. The ring joint is a new connection method used for the vertical connection. Few studies and related regulations were traced; therefore more detailed studies are required. In order to study the anchoring performance and failure behavior, an experimental model was designed and tested under monotonic axial loading, taking the composite height of ring rebars, concrete specifications, diameter of the horizontal rebars, relative position of the ring rebars, diameter of the ring rebars, and number of horizontal rebars into consideration. The failure phenomena were observed and the data were collected. The failure pattern, bearing capacity, yield ratio, displacement ductility coefficient, and other performance parameters were analyzed. The study indicated that the failure patterns are divided into ring rebar pull-out and ring rebar fracture. Increasing the composite height of the ring rebar, the concrete specifications and the number of horizontal rebars could improve the bearing performance, and the contribution of the horizontal rebar diameter was limited, and interlocking ring rebars arranged uniformly are not optimal. In the case of joint failure, the yield ratio is relatively small and the displacement ductility coefficient is larger, which shows the bearing capacity reserve is better. A numerical model was established to analyze the internal behavior, and the results were in good agreement with the experimental results, important for us to understand the failure behavior. Design recommendations will promote its application.